Venous Thrombotic Risk in Family Members of Unselected Individuals with Factor V Leiden - Lensen, R. P. M.; Bertina, R. M.; de Ronde, H.; Vandenbroucke, J. P.; Rosendaal, F. R. (Thrombosis and Haemostasis, 2000)
The factor V Leiden mutation (FVL) leads to a seven-fold increased risk of venous thromboembolism (VTE). In thrombophilic families, 25% of carriers have experienced thrombosis before the age of 40 years. Aim of our study was to assess the association of FVL with VTE in first-degree family members of unselected symptomatic and asymptomatic carriers of FVL.We tested 197 relatives of consecutive thrombosis patients with FVL and 36 relatives of asymptomatic carriers on the presence of FVL and the occurrence of VTE.The incidence of VTE in relatives with FVL of symptomatic carriers was 0.34%/year. This was similar to the incidence in relatives with FVL of asymptomatic carriers. Kaplan Meier analysis in relatives of symptomatic propositi showed that at the age of 58 years, thrombosisfree survival was reduced to 75% in carriers and 93% in non-carriers (P < 0.05). Carriers of FVL had a three times higher thrombotic risk than non-carriers. In combination with environmental risk factors, FVL clearly adds to the risk of VTE. The thrombotic incidence rate in these unselected relatives with FVL, however, is considerably lower than was seen in carriers of thrombophilic families (1.7%/year). Therefore, special care should be paid to individuals with a positive family history of venous thrombosis while exposed to these risk factors.
Keywords: Venous thromboembolism; thrombophilia; Factor V Leiden; hypercoagulability